Bahasa Inggris: Bahasa Inggris - Maghfiroh, Naela; Cahyono, Guntur (Rabbani: Jurnal Pendidikan Agama Islam, 2022)
ABSTRACT: This research was studied starting from the view that the creativity possessed by a santri is limited because the activities in which are dominated by generations with its distinctive series, which are traditional. However, after looking at the future, many Islamic boarding schools are currently modifying their education system with various activities such as extracurricular activities. This study aims to determine the effect of the pesantren environment and the activity of participating in extracurricular activities on the creativity of students at the Edi Mancoro Islamic Boarding School. The number of samples in this study were 30 students. The research method that the author uses in this research is quantitative research. The results of the research are: 1) The pesantren environment has a positive and significant effect on the creativity of students, 2) The activity of participating in extracurricular activities has a positive and significant effect on the creativity of students, 3) The pesantren environment and active participation in extracurricular activities simultaneously affect the creativity of students, 4) Values R Square shows the ability of the pesantren environment variable and the activeness to participate in extracurricular activities in explaining the students' creativity variable is 0.368 or 36.8%.